Visualisation for ontology sense-making: A tree-map based algorithmic approach - Vidanage, Kaneeka; Mohamad Noor, Noor Maizura; Mohemad, Rosmayati; Bakar, Zuriana Abu (Institute of Advanced Engineering and Science, 2021)
Ontology sense-making or visual comprehension of the ontological schemata and structure are vital for cross-validation purposes of the ontology increment during the process of applied ontology construction. Also, it is important to query the ontology in order to verify the accuracy of the stored knowledge embeddings. This will boost the interactions between domain specialists and ontologists in applied ontology construction processes. Hence existing mechanisms have numerous of deficiencies (discussed in the paper), a new algorithm is proposed in this research to boost the efficiency of usage of tree-maps for effective ontology sense making. Proposed algorithm and prototype are quantitatively and qualitatively assessed for their accuracy and efficacy.